2017
DOI: 10.1186/s12883-017-0863-9
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic biomarker profile for fibromyalgia syndrome based on an NMR metabolomics study of selected patients and controls

Abstract: BackgroundFibromyalgia syndrome (FMS) is a chronic pain syndrome. A plausible pathogenesis of the disease is uncertain and the pursuit of measurable biomarkers for objective identification of affected individuals is a continuing endeavour in FMS research. Our objective was to perform an explorative metabolomics study (1) to elucidate the global urinary metabolite profile of patients suffering from FMS, and (2) to explore the potential of this metabolite information to augment existing medical practice in diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 35 publications
6
70
0
2
Order By: Relevance
“…According to the investigators, lysophosphocholine dominated the metabolite profile, suggesting that there may be additional potential biomarkers for FM diagnosis (17). Recently, Malatji et al (18) used NMR metabolomics to identify a diagnostic biomarker profile for FM from urine, identifying metabolites associated with indicators of pain and fatigue symptoms (succinic acid, taurine, and creatine) and perturbations in the gut microbiome (hippuric, 2-hydroxyisobutyric, and lactic acids).…”
mentioning
confidence: 99%
“…According to the investigators, lysophosphocholine dominated the metabolite profile, suggesting that there may be additional potential biomarkers for FM diagnosis (17). Recently, Malatji et al (18) used NMR metabolomics to identify a diagnostic biomarker profile for FM from urine, identifying metabolites associated with indicators of pain and fatigue symptoms (succinic acid, taurine, and creatine) and perturbations in the gut microbiome (hippuric, 2-hydroxyisobutyric, and lactic acids).…”
mentioning
confidence: 99%
“…1) shows the selection process and number of studies included and excluded at each step to arrive at the final eleven studies, conducted in 7 countries, included in this analysis. There was a high degree of heterogeneity across the studies, which were of variable quality ( (22)(23)(24)(25), and three reported other biomarkers (16,21,26). Four studies (16,(21)(22)(23) examined more than one type of biomarker and so are included in each of the appropriate sections below.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, we found elevated levels of taurine, a sulfur-containing amino acid whose pathway is understood to be associated with alterations in lipid metabolism in women. 29 Elevated levels of taurine have been previously reported in serum 30,31 and urine 32 in women diagnosed with FM. Similarly, elevated levels of methionine sulfoxide and anthranilate have been reported.…”
Section: Metabolomic Differentials In Fibromyalgiamentioning
confidence: 89%